2020
DOI: 10.20944/preprints202010.0651.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of Pre-Exam Anxiety on the Academic Performance of Final Year Medical Students

Abstract: Introduction: Exams are a relatively stressful period for all students, especially undergraduate medical students. Exams bring anxiety and stress for the students. Some students experience such high stress that it hinders their academic productivity and reduces their exam performance. The aim of this study is to assess the effects of pre-exam anxiety on the academic performance of medical students. Methods: Two hundred and twenty-five final year medical students completed Westside Test Anxiety (WTA) Scale one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…However, with alternative assessments, students were able to perform at their best-stress reduction, think critically-which resulted in high performance. These findings were illustrated in the qualitative data and confirm the work of Sohail et al (2020) which reported that stress has negative impact on the academic performance of students, but in contrast to the work of Dawood et al (2016), they found no relationship between test anxiety and academic performance. Despite either opinion, as future work skills are moving from task-orientation to critical and problem-solving orientation, assessment designs should be authentic and reflect current industry practices.…”
Section: Discussionsupporting
confidence: 81%
“…However, with alternative assessments, students were able to perform at their best-stress reduction, think critically-which resulted in high performance. These findings were illustrated in the qualitative data and confirm the work of Sohail et al (2020) which reported that stress has negative impact on the academic performance of students, but in contrast to the work of Dawood et al (2016), they found no relationship between test anxiety and academic performance. Despite either opinion, as future work skills are moving from task-orientation to critical and problem-solving orientation, assessment designs should be authentic and reflect current industry practices.…”
Section: Discussionsupporting
confidence: 81%